INFLUENCE AND ROLE OF ENTERPRISE RISK MANAGEMENT IN BUSINESS CONTINUITY DURING THE COVID-19 PANDEMIC AND ITS IMPACT ON POLICY MAKING FROM MAIN STAKEHOLDERS ON MSMEs IN INDONESIA AS AN INTERVENING VARIABLE - Lambok Rommy Sulaeman; Nurali Nurali; Rizaldi Putra (Jurnal Ekonomi, 2023)
The economic impact of the COVID-19 pandemic has been felt by the Micro, Small and Medium Enterprises (MSMEs) sector. This is because Micro, Small and Medium Enterprises occupy a strategic position in the economy in general and are one of the strategic sectors in the national economy which can be seen from the employment absorption. Small businesses have been among the hardest hit by the COVID-19 crisis, many have temporarily closed their businesses, and are further facing cash flow constraints. This study aims to look at the Influence and Role of Enterprise Risk Management in Business Continuity During the Covid-19 Pandemic and Its Impact on Policy Making from Key Stakeholders in MSMEs in Indonesia as an intervening variable. This research is a quantitative type using a sample of 133 respondents, sample selection using purposive sampling technique. The results of this study are the t statistics value of 3.774 > t table = 1.97838 , and the P-Values = 0.000 <from α = 0.05 means the ERM variable has a positive and significant influence on the variable of decision making ; the t statistics value is 2.835 > t table = 1.97838, and the P-Values = 0.005 <from α = 0.05 means that the decision-making variable has a positive and significant influence on business continuity variables ; the t statistics value is 2.440 > t table = 1.97838 , and the P-Values = 0.0 15 <from α = 0.05 means that the ERM variable has a positive influence on the business continuity variable through policy making .